h - Campos, Pedro; Graham, Nicholas; Jorge, Joaquim; Nunes, Nuno.; Palanque, Philippe; Winckler, Marco; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The four-volume set LNCS 6946-6949 constitutes the refereed proceedings of the 13th IFIP TC13 International Conference on Human-Computer Interaction, INTERACT 2011, held in Lisbon, Portugal, in September 2011. ((Text folgt)) The 49 papers included in the second volume are organized in topical sections on health, human factors, interacting in public spaces, interacting with displays, interaction design for developing regions, interface design, international and culural aspect of HCI, interruptions and attention, mobile interfaces, multi-modal interfaces, multi-user interaction/cooperation, and navigation and wayfinding.
Keywords: Computer science; Software engineering; Information systems; Artificial intelligence; Education; Computer Science; User Interfaces and Human Computer Interaction; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Computers and Education; Computers and Society; Software Engineering